Transversus abdominis plane block : the holy Grail of anaesthesia for (lower) abdominal surgery - Janković, Zorica, liječnica (Array, 2009)
The transversus abdominis plane (TAP) block is a new, rapidly expanding regional anaesthesia technique that provides analgesia following abdominal surgery. It involves a single large bolus injection of local anaesthetic into the TAP, an anatomical space between the internal oblique and transversus abdominis muscles. This article presents the development of the TAP block over the last 10 years, with an analysis of all anatomical and case studies and randomized controlled trials, and an account of the author’s own experience.